Epibionts and Epiphytes in Seagrass Habitats: A Global Analysis of Their Ecological Roles - Nicoletta Marsiglia; Mar Bosch-Belmar; Francesco Paolo Mancuso; Gianluca Sarà (Sci, 2025)
Seagrass ecosystems support complex biological interactions that shape marine community structure and ecosystem functioning. Thanks to their structural complexity, they support heterogeneous communities and interact with associated benthic invertebrates and fish populations, establishing complex relationships that influence the performance and fitness of the involved organisms. This study, through a systematic review, investigated the existing potential biotic interactions between seagrasses and epibionts–epiphytes on a global scale. We created a complex search string and ran it in the online databases Scopus and Web of Science, yielding a total of 62 final outcomes spanning from 1984 to 2024. Our results revealed both positive and negative effects of different biotic interactions among these habitat formers and their associated symbionts. The review showed that the most studied interactions referred to Posidonia oceanica (Delile, 1813) L. and Zostera marina (Linnaeus, 1753), which provide refuge and habitat to different epiphytes and epibionts. The reviewed studies highlighted the importance of epiphytes, their potential role in seagrass growth, nutrient dynamics, and their implications for light absorption, while epibionts enhance canopy structure and can protect seagrasses from predation, but potential drawbacks remain poorly understood. Understanding and preserving these intricate biotic interactions is critical to ensuring the long-term functionality and resilience of seagrass ecosystems in a continuously changing environment.